Effectiveness of the PjBL Model Assisted by Differentiated Teaching Materials to Improve Students' Cognitive and Creative Thinking Skills - Desmitha Prafitri Alwi; Parlindungan Sinaga; Lina Aviyanti (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of this study was to measure the effectiveness of the PjBL model assisted by differentiated teaching materials in improving students' cognition and creativity. This research aims to evaluate the effectiveness of the Project Based Learning (PjBL) model assisted by differentiated teaching materials in improving students' cognitive abilities and creative thinking skills on temperature and heat material. This research uses a quasi-experimental method with a pretest-posttest control group design. The research sample consisted of two classes in one high school in Indonesia, with one class as an experimental group using PjBL assisted by differentiated teaching materials, and one class as a control group using conventional learning methods. Data was collected through cognitive ability tests, creative thinking skills tests, student motivation and engagement questionnaires, as well as interviews with teachers and students. The research results show that the PjBL model assisted by differentiated teaching materials significantly improves students' cognitive abilities and creative thinking skills compared to conventional learning methods. In addition, students in the experimental group also showed higher motivation and involvement in the learning process. Interviews with teachers and students revealed that the learning experience using this model was very positive, with students feeling more engaged and teachers seeing improvements in student learning outcomes.